Emotional Connection, Social Interaction, and Content Performance Quality in Building Fan Loyalty on Indonesian Indie Music Streaming Platforms - Sarifiyono, Aggi Panigoro; Purnama, Susan; Anang Bambang Pujianto; Johnson Sinaga; Ade Sintia Hendrian (Yayasan Sinergi Kawula Muda, 2025)
The rapid evolution of digital technologies has reshaped the global music industry, particularly through streaming platforms. This research examines the optimization of fan loyalty within Indonesia’s indie music scene on platforms like Spotify and YouTube Music by analyzing the influence of emotional connection, social interaction, and content performance quality. Using a descriptive-verifiable research design and Structural Equation Modeling (SEM) with 300 streaming platform users, the study finds that these factors significantly impact satisfaction, engagement, and perceived value, ultimately driving fan loyalty. Satisfaction acts as a critical mediator, reinforcing its role in loyalty formation. The findings offer strategic insights for indie artists and streaming platforms, emphasizing the importance of personalized content, community-driven features, and high-quality production in fostering deeper fan engagement and ensuring long-term sustainability in the digital music industry.